Neonatal Intensive Care and Child Psychiatry Inpatient Care: Do Different Working Conditions Influence Stress Levels? - Evalotte Mörelius; Per A. Gustafsson; Kerstin Ekberg; Nina Nelson (Nursing Research and Practice)
Introduction. Nurses often experience work-related stress. High stress can negatively affect job satisfaction and lead to emotional exhaustion with risk of burnout. Aim. To analyse possible differences in biological stress markers, psychosocial working conditions, health, and well-being between nurses working in two different departments. Methods. Stress was evaluated in nurses working in a neonatal intensive care unit (NICU) (n=33) and nurses working in a child and adolescent psychiatry inpatient ward (CAP) (n=14) using salivary cortisol and HbA1c. Salivary cortisol was measured three times a day on two consecutive days during two one-week periods, seven weeks apart (= 12 samples/person). Psychosocial working conditions, health, and well-being were measured once. Results. NICU nurses had better social support and more self-determination. CAP nurses had a lower salivary cortisol quotient, poorer general health, and higher client-related burnout scores. Conclusion. When comparing these nurses with existing norm data for Sweden, as a group their scores reflect less work-related stress than Swedes overall. However, the comparison between NICU and CAP nurses indicates a less healthy work situation for CAP nurses. Relevance to Clinical Practice. Healthcare managers need to acknowledge the less healthy work situation CAP nurses experience in order to provide optimal support and promote good health.